2013
DOI: 10.1080/15287394.2013.827996
|View full text |Cite
|
Sign up to set email alerts
|

Two Generations of Fall Armyworm (Lepidoptera: Noctuidae) Contamination by Di-n-Butylphthalate

Abstract: The effects of di-n-butylphthalate (DnBP) were investigated with respect to bioaccumulation and whether these effects occurred over a second generation in the fall armyworm Spodoptera frugiperda (J.E. Smith, 1797). The concentrations of DnBP in males and females of the second generation were higher than those in first one. However, frequency of mortality of exposed individuals in the second generation was approximately 57% less but the reduction in size and weight was more pronounced than in the first generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…PAE produce reproductive and developmental toxicities, among other adverse health effects (Autian, 1973;Hill et al, 2003;Koo and Lee, 2005;Chung et al, 2013;Bhat et al, 2014;Guerra et al, 2014). Several in vitro and in vivo toxicological studies demonstrated a wide range of systemic and target organ toxicities (Filho Ido et al, 2013;Yoon et al, 2014). Phthalic acid (PA) is a final common metabolite of phthalates including diethyl hexylphthalate (DEHP), dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), and diethyl phthalate (DEP) (Albro et al, 1987) ( Figure 1).…”
mentioning
confidence: 96%
“…PAE produce reproductive and developmental toxicities, among other adverse health effects (Autian, 1973;Hill et al, 2003;Koo and Lee, 2005;Chung et al, 2013;Bhat et al, 2014;Guerra et al, 2014). Several in vitro and in vivo toxicological studies demonstrated a wide range of systemic and target organ toxicities (Filho Ido et al, 2013;Yoon et al, 2014). Phthalic acid (PA) is a final common metabolite of phthalates including diethyl hexylphthalate (DEHP), dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), and diethyl phthalate (DEP) (Albro et al, 1987) ( Figure 1).…”
mentioning
confidence: 96%